The Role Anesthesia in Mortality and Morbidity due to the Medical Malpractice - Ertan, Ayşegül; Öz, Hüseyin (The Bulletin of Legal Medicine, 2006)
A significant increase in the lawsuits against physicians and other healthcare professionals with the claim of anesthesia malpractice has been observed. Retrospective studies about perioperative deaths show that the most common causes of the deaths are the patients’ preoperative diseases and surgical intervention itself. Besides this, undesirable conditions related to anesthesia practice mostly occur due to human mistakes. Standardized monitoring, continuing education, improving the working conditions, feedback from the medical practice lawsuits, standardized care guidelines on anesthesiology practice and crisis management are of critical importance for reducing the medical malpractice claims, especially those of the preventable anesthesia accidents.Key words: Anesthesia, medical malpractice
Keywords: anesthesia; medical malpractice